Analysis of exergy and heat transfer in a tube fitted with flapped V-baffles - Jayranaiwachira, Nuthvipa; Promvonge, Pongjet; Tongyote, Paritkavin; Skullong, Sompol; Nakhchi, Mahdi Erfanian (My University, 2024)
Vortex generator is a device that shows promise in generating streamwise vortices that can be utilized for boosting the rate of heat transmission inside a cooling/heating system with a relatively smaller penalty in terms of friction loss. The primary goal of the current research is to maximize the comparative Nusselt number ratio (Nu/Nu0) to be as large as possible to lower the size of the system while keeping thermal performance as high as feasible to save more energy. Thus, in the current study, the impacts of inserting the flapped V-baffle vortex generator (FBVG) on the thermal effectiveness improvement of a round tube were experimentally investigated. At a fixed attack angle (α = 60°) and baffle blockage ratio (BR = b/D = 0.3), the geometrical behaviors of FBVGs placed periodically along two edges of a straight tape were six different flap angles (θ = 0°, 25°, 35°, 45°, 65° and 90°) and three ratios of baffle pitches (P/D = PR = 2.0, 1.5, and 1.0). The current V-baffles, which were positioned on both tape edges, were designed to reduce friction loss caused by interrupting the central core flow when placed on both tape sides. The measurement results focused on the friction loss and thermal behaviors, including exergy and entropy analyses for Reynolds number from 4750 to 29,270. In the findings, the Nusselt number and friction factor of FBVG at θ = 0° and PR = 1 are, respectively, up to 5.6 and 35.24 times larger than those of the smooth tube. The entropy generation (S˙gen′) seems to decline as θ and PR increase, with the smallest S˙gen′ found at θ = 0° and PR = 1 for lower Re. The FBVG has the greatest exergy efficiency (ηEx) at θ = 0° and PR = 1. To find the true benefits of FBVG, its thermal performance is estimated and seen to reach a maximum at about 2.44 with NuR = 4.65 at θ = 45° and PR = 1. The optimal scenario at θ = 25° and PR = 1 was preferred, however, since it yielded the largest NuR = 5.42 at TEF = 2.39.
Keywords: Entropy generation; Exergy efficiency; Heat exchanger; Thermal performance; Vortex generator